Topological characterization of a bacterial cellulose-acrylic acid polymeric matrix - N. Halib; Amin, MCIM; Ahmad, I; Abrami, M; Fiorentino, S; Farra, R; Grassi, G; Musiani, F; Lapasin, R; Grassi, M (Elsevier, 2024)
Indexed by WOS/ Scopus